Power system load flow analysis based on fast decoupled method using Microsoft Excel / Muhammad Azri Mohd Zawawi - Mohd Zawawi, Muhammad Azri (2014)
This thesis presents a development of a Power System Load Flow Analysis based on Fast Decoupled Method using Microsoft Excel. It is designed to solve a load flow problem with mathematical calculations which are difficult to solve by hand calculation. This educational toolbox will help to facilitate undergraduate electrical studies to determine the value of voltage (V), voltage angle (8), real power (P) and reactive power (Q) of each bus. Load flow toolbox is evaluated by solving the load flow of several test systems including IEEE bus system. The solution is verified with well known load flow analysis software such as Microsoft Excel, Power World Simulator, MATLAB and PSS Adept. The comparison results show the accuracy of the load flow toolbox developed using the Microsoft Excel.